2020
DOI: 10.15252/embj.2020105220
|View full text |Cite
|
Sign up to set email alerts
|

IL‐2/IL‐7‐inducible factors pioneer the path to T cell differentiation in advance of lineage‐defining factors

Abstract: When dormant naïve T cells first become activated by antigenpresenting cells, they express the autocrine growth factor IL-2 which transforms them into rapidly dividing effector T cells. During this process, hundreds of genes undergo epigenetic reprogramming for efficient activation, and also for potential reactivation after they return to quiescence as memory T cells. However, the relative contributions of IL-2 and T cell receptor signaling to this process are unknown. Here, we show that IL-2 signaling is requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 94 publications
(191 reference statements)
5
31
0
Order By: Relevance
“…In this study, Tem cells exhibit much higher expression of the Il7r, IL2ra and Il2b genes than Tcm cells (Figures 7A-C) consistent with the previous observation that Tcm cells lack IL-2Ra expression (5,26). This is highly significant because we recently demonstrated that IL-2/IL-7 signalling via the common gamma chain plays a crucial role in maintaining accessible sites in lineage-specific genes prior to T cell differentiation (5). Without this priming for T cell differentiation, Tcm cells may be left in limbo, unable to differentiate, but progress towards an equally important fate of establishing and maintaining a plastic memory of TCR activation, before any lineage-commitment decision has been made.…”
Section: The Choice Of Cytokine Receptors Influences the Decision Between Tem And Tcm Commitmentsupporting
confidence: 92%
See 3 more Smart Citations
“…In this study, Tem cells exhibit much higher expression of the Il7r, IL2ra and Il2b genes than Tcm cells (Figures 7A-C) consistent with the previous observation that Tcm cells lack IL-2Ra expression (5,26). This is highly significant because we recently demonstrated that IL-2/IL-7 signalling via the common gamma chain plays a crucial role in maintaining accessible sites in lineage-specific genes prior to T cell differentiation (5). Without this priming for T cell differentiation, Tcm cells may be left in limbo, unable to differentiate, but progress towards an equally important fate of establishing and maintaining a plastic memory of TCR activation, before any lineage-commitment decision has been made.…”
Section: The Choice Of Cytokine Receptors Influences the Decision Between Tem And Tcm Commitmentsupporting
confidence: 92%
“…Once immunological memory has been established in T cells, it is remarkably stable in the absence of further TCR activation. In rapidly dividing cells cultured with IL-2 or IL-7, mDHSs recruit TFs that include ETS1, RUNX1, JUND and STAT5 which maintain an open chromatin environment rendered more accessible by histone H3K4me2 and H3K9ac (3,5). In the context of immune homeostasis, immunological priming of TM cells is likely to remain stable for decades in quiescent TM cells in the presence of lymph node derived IL-7 or tissue-derived IL-15 (5,(10)(11)(12).…”
Section: Immunological Memory Is Established Within 7 Days and Remains Stablementioning
confidence: 99%
See 2 more Smart Citations
“…The roles of STATs in both limiting and promoting gene expression became clear by the demonstration that STATs can also lead to unloading of p300 at enhancers of opposite lineages. Other reports suggest that IL‐2 signaling is essential for maintaining accessible chromatin regions at hundreds of gene regulatory elements of T cell differentiation pathways 141 . More specifically, IL‐2 signaling can activate AP‐1 and STAT5 proteins that can subsequently bind lineage‐determining transcription factors, depending on other proteins downstream of extracellular environments of T cells.…”
Section: Transcription Factors As Genome Organizers In T Lymphocytesmentioning
confidence: 99%